Online teaching for cell culture techniques as a new paradigm: a review / Noor Fahitah Abu Hanipah, Siti Norashikin Mohd Tambeh and Wan Nor I’zzah Wan Mohamad Zain - Abu Hanipah, Noor Fahitah; Mohd Tambeh, Siti Norashikin; Wan Mohamad Zain, Wan Nor I’zzah (UiTM Press, 2023)
Due to its vast application in life sciences, cell culture is one of the modes of choice for research and has been used extensively in antibody, vaccine and hormone production. Techniques in cell culturing are traditionally learnt hands-on in the laboratory setting. Instructors demonstrate the cell culturing techniques for students to emulate or re-perform. However, the lack of trained instructors, limited number of equipment and increased costs are major hindrances in hands-on learning of cell culture techniques. Online learning was initially necessitated for instructors by the unprecedented event of COVID-19 pandemic worldwide which led to the limitations in conducting practical and hands-on sessions. In this review, various teaching and learning methods which include blended learning, virtual laboratory, or massive online open course (MOOC), and assessment modalities related to online teaching of cell culture techniques are discussed. The benefits of these modalities to students and instructors such as increased motivation and more engaged learning are discussed.